The Influence of Perceived Value in the Coffee Shop Industry in Jakarta on Customer Loyalty - Virginia Balqqis Zacqualine; Ailen Tania; Hermanto Yaputra; Steven Tanjaya; Vebrina Anggraini Tambunan (Jurnal Visi Manajemen, 2025)
This study aims to analyze the influence of perceived value on customer loyalty in the coffee shop industry in Jakarta by considering the role of customer satisfaction as a mediating variable. The approach used is quantitative with Partial Least Square (PLS) analysis technique. Perceived value includes dimensions of perceived quality, customer expectations, social value, and emotional value. The results show that all dimensions of perceived value have a significant effect on customer satisfaction. Furthermore, customer satisfaction is proven to have an important role in increasing loyalty, where emotional and social experiences are factors that are no less important than functional aspects. The novelty of this study lies in the integration of emotional and social dimensions in explaining customer loyalty. The practical implication is that coffee shop business actors can develop service strategies that are more focused on creating meaningful customer experiences. Future research is recommended to explore qualitative approaches to understand the dynamics of consumer behavior in the context of urban lifestyles.